A Self‐Assembled Fmoc‐Diphenylalanine Hydrogel‐Encapsulated Pt Nanozyme as Oxidase‐ and Peroxidase‐Like Breaking pH Limitation for Potential Antimicrobial Application. Issue 26 (29th March 2022) - Chen, Jun; Zhang, Shuo; Chen, Xu; Wang, Lianying; Yang, Wensheng
Abstract: Nanomaterials with oxidase‐ and peroxidase‐like activities have potential in antibacterial therapy. The optimal activity of most nanozymes occurred in acidic pH (3.0–5.0), while the pH in biological systems is mostly near neutral. Herein, a general system using 9‐fluorenylmethoxycarbonyl‐modified diphenylalanine (Fmoc‐FF) hydrogel for enhancing oxidase‐ and peroxidase‐like activities of Pt NPs and other typical enzyme‐like nanomaterials at neutral or even alkaline pH is proposed. In this system, Fmoc‐FF hydrogel provides an acidic microenvironment for Pt NPs due to hydrogen protons (H + ) produced by the dissociation of F at neutral pH. As a result, Pt NPs exhibits 6‐fold enhanced oxidase‐like and 26‐fold peroxidase‐like activity after being encapsulated into Fmoc‐FF hydrogel at pH 7.0. Based on outstanding enzymatic activities and the antibacterial activity of Fmoc‐FF hydrogel itself, Pt‐Fmoc‐FF hydrogel realizes excellent antibacterial effect. This design provides a universal strategy to break pH limitation of nanozymes and promotes the biological applications of nanozymes. Abstract : Pt‐Fmoc‐FF hydrogel was found for the first time that it has both significantly enhanced oxidase‐like (OXD‐like) and peroxidase‐like (POD‐like) activities at neutral pH. The strategy of dissociating H + from Fmoc‐FF at neutral pH break pH limit and has a universal effect on nanomaterials with oxidase‐ or peroxidase‐like over a wide pH range, this work accelerates the application of nanozymes in biological system.